2006
DOI: 10.1016/j.biochi.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) and manganese(III) complexes of N′-[(2-hydroxy phenyl) carbonothioyl] pyridine-2-carbohydrazide: novel therapeutic agents for cancer

Abstract: c-Src is a non-receptor tyrosine kinase which plays a significant role in the growth mediated signaling pathway impacting cellular proliferation, differentiation, mobility, survival and transformation. Myristoylation of pp60(c-src) leads to its membrane association and activation, a process catalyzed by N-myristoyltransferase (NMT). We have shown earlier increased NMT activity in the early stages of colon cancer. A novel sulfur nitrogen donor ligand and its Cu(II) and Mn(III) complexes have been prepared and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Our results suggest that another aspect of the NIP71/hsc70 overexpression could be to regulate elevated NMT activity in tumor cells. It has recently been shown that the knock down of NMT results in apoptosis (31,32). Our results suggest a novel relationship of NIP71/hsc70 and NMT and assign an important function of NIP71/hsc70 to regulate NMT activity in OSCC.…”
Section: Resultssupporting
confidence: 54%
“…Our results suggest that another aspect of the NIP71/hsc70 overexpression could be to regulate elevated NMT activity in tumor cells. It has recently been shown that the knock down of NMT results in apoptosis (31,32). Our results suggest a novel relationship of NIP71/hsc70 and NMT and assign an important function of NIP71/hsc70 to regulate NMT activity in OSCC.…”
Section: Resultssupporting
confidence: 54%
“…The aromatic protons were observed in the range of 7.23-8.72 ppm. Assignment of the 13 C NMR spectral data of the ligands is based on 13 C shifts in similar hydrazone ligands [38,40]. The signals observed at 163.72 and 153.66 ppm in H 2 L 1 ligand and 156.7 and 151.62 ppm in H 2 L 2 ligand can be assigned to C=O and C=N, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Four human alimentary system carcinoma cell lines, SGC7901 (gastric tumor cell line), EC109 (esophagus tumor cell line), SMMC7721 (liver tumor cell line), and HT29 (colon tumor cell line), were utilized in our work. These cell lines were chosen to explore the potential selectivity of our copper(II) complexes towards different human alimentary system carcinoma cell lines and all have been previously used in studies with copper complexes that are cytotoxic [18][19][20][21]. IC 50 values indicated that 2 and 3 have promising cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%